Depletion of METTL3 alters cellular and extracellular levels of miRNAs containing m6A consensus sequences. Issue 12 (December 2021) - Abner, Jessica J.; Franklin, Jeffrey L.; Clement, Margaret A.; Hinger, Scott A.; Allen, Ryan M.; Liu, Xiao; Kellner, Stefanie; Wu, Junzhou; Karijolich, John; Liu, Qi; Vickers, Kasey C.; Dedon, Peter; et al.
Abstract: Extracellular vesicles (EVs) are capable of transferring cargo from donor to recipient cells, but precisely how cargo content is regulated for export is mostly unknown. For miRNA cargo, we previously showed that when compared to isogenic colorectal cancer (CRC) cells expressing wild-type KRAS, a distinct subset of miRNAs are differentially enriched in EVs from KRAS mutant active CRC cells, with miR-100 being one of the most enriched. The mechanisms that could explain how miR-100 and other miRNAs are differentially exported into EVs have not been fully elucidated. Here, we tested the effect of N 6 -methyladenosine (m 6 A) modification on miRNA export into EVs by depletion of METTL3 and ALKBH5, a writer and eraser of m 6 A modification, respectively. While the effects of ALKBH5 knockdown were quite modest, decreased levels of METTL3 led to reduced cellular and extracellular levels of a subset of miRNAs that contain consensus sequences for m 6 A modification. Functional testing of EVs prepared from cells expressing shRNAs against METTL3 showed that they were less capable of conferring colony growth in 3D to wild-type KRAS cells and were also largely incapable of conferring the spread of cetuximab resistance. Our data support a role for METTL3 modification on cellular miRNA levels and export of specific miRNAs. Abstract : miRNA, Base modification, Extracellular vesicle, m 6 A, RNA, Tumor microenvironment